STRATEGI KEBERLANJUTAN PENGEMBANGAN ENERGI LOKAL MELALUI PROGRAM BIOGAS RUMAH DI DESA TONJONG BOGOR - Muhiroh; Muhtadi (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2023)
The study is backfaced by the limited and costly sources of cooking energy in Indonesia and the ephesically inadequate stockpile of cattle dung. Yayasan Rumah Energi (YRE) created a social program to minimize the problem, one of which is a Biogas Rumah program (BIRU). The purpose of this research was to learn YRE sustainability strategies through the BIRU program, contributing factors and BIRU program in hibitors in the village of Tonjong Bogor. The study in this time involves qualitative research methods, the techniques used of observation, interviews, the study of documentation, and the use of data validity data triangulation. Based on field findings, it may be known that YRE sustainability strategies through the BIRU program are found in 3 aspects, which are 1) Economic sustainability, 2) Environmental sustainability, and 3) Social sustainability. The results of this study are YRE sustainability strategies found in 3 aspects, 1) Economic sustainability, empowering communities through biogas and bio-slurry and producing domessomen. 2) Environmental sustainability, propagating biogas instead of petroleum and gas. 3) Social sustainability, giving knowledge about biogas and opening jobs in the construction field. The underlying factors are the availability of the main ingredients in biogas production, the availability of land to build biogas reactors and the support of governments and other agencies. While the constraining factor is the absence of the cost of building biogas reactors, the lack of interest in people using biogas, and some governments still do not support it.